PENGARUH BRAND LOVE DAN BRAND IDENTIFICATION TERHADAP PURCHASE INTENTION MELALUI SELF CONGRUITY SEBAGAI VARIABEL MEDIASI - Situmorang, Grece Simon Situmorang; Iqbal Daulay, M.Yasser (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
ABSTRACT This research aims to examine the influence of brand love and brand identification on purchase intention through self-congruity as a mediating variable among Erigo product users in Bengkulu City. Brand love is the strong and positive feeling that consumers have towards a brand, while brand identification is the process by which consumers associate themselves with a brand. Purchase intention is the consumer's desire to buy a product or service from a brand, and self-congruity is the suitability between the consumer's self-image and the brand image. This research used a survey method by distributing questionnaires to 259 respondents who were users of Erigo products in Bengkulu City. The data processing technique uses Structural Equation Modeling (SEM) analysis with the help of SmartPLS. The research results show that brand love and brand identification have a positive and significant effect on purchase intention, both directly and indirectly through self-congruity. Keywords: Brand Love, Brand Identification, Purchase Intention, Self Congruity